2010
DOI: 10.1088/0951-7715/23/11/005
|View full text |Cite
|
Sign up to set email alerts
|

Intersections of homogeneous Cantor sets and beta-expansions

Abstract: Let Γ β,N be the N -part homogeneous Cantor set with β ∈ (1/(2N − 1), 1/N ).is called a code of t. Let U β,±N be the set of t ∈ [−1, 1] having a unique code, and let S β,±N be the set of t ∈ U β,±N which make the intersection Γ β,N ∩ (Γ β,N + t) a selfsimilar set. We characterize the set U β,±N in a geometrical and algebraical way, and give a sufficient and necessary condition for t ∈ S β,±N . Using techniques from beta-expansions, we show that there is a critical point βc ∈ (1/(2N − 1), 1/N ), which is a tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…The number q KL is called the Komornik-Loreti constant; see Section 2 below for a precise definition. The above result was generalized to arbitrary M ≥ 1 by Baker [7] and Kong et al [22].…”
Section: Introductionmentioning
confidence: 89%
“…The number q KL is called the Komornik-Loreti constant; see Section 2 below for a precise definition. The above result was generalized to arbitrary M ≥ 1 by Baker [7] and Kong et al [22].…”
Section: Introductionmentioning
confidence: 89%
“…[16], see also, [22]). One might expect that for each connected component (q 0 , q * 0 ) of (q c , M + 1] \ U , the closed interval [q 0 , q * 0 ] would be an entropy plateau of H. However this is not true.…”
mentioning
confidence: 86%
“…Later, Glendinning and Sidorov [12] showed that U q is countably infinite for q G < q < q KL ; uncountable but of zero Hausdorff dimension for q = q KL ; and of positive Hausdorff dimension for q > q KL . These results were generalized to larger alphabets by Baker [6] and Kong, Li and Dekking [17]. Kong and Li [16] further examined the Hausdorff dimension of U q , and more recently, Komornik, Kong and Li [13] showed that this dimension is related to the topological entropy of the symbolic univoque set…”
Section: Introductionmentioning
confidence: 95%